Realization of two dimensional MEMS based displays using polymer composite micro-scanners integrated with one dimensional polymer LED arrays - Gökdel, Yiğit Dağhan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
A novel type of displays are realized by hybrid and monolithic integration of optoelectronic devices with micro electro mechanical systems (MEMS). MEMS platform, with mechanical quality factor (20-50 in air) enhanced displacement, defines the refresh rate of the two-dimensional display. Vertical resolution of the display is increased by operating the MEMS device at its fundamental resonance mode. Actuation of this mechanical mode is accomplished by generating a time and frequency dependant electromagnetic force or torque on the MEMS platform. Horizontal scan of the display is performed by modulation of a one dimensional array of light emitting diodes. In effect, a LED emitter moving in the direction of vertical scan, generates a virtual pixel whose brightness is electronically modulated. First prototype which is realized in this thesis work is an inorganic LED integrated FR4 display, where modulation of light sources is synchronized with FR4 movement. Performance metrics of this prototype with LED driving integrated circuits on, are 3.4 mm of peak resonant displacement, two orders of magnitude suppression of the second parasitic mode. The prototype, composed of all polymer materials utilizes ITO - PEDOT:PSS - MEH-PPV and FR4. Magnetic actuator is integrated with the polymer LED devices and two-dimensional display functionality is demonstrated. Realized display has 20 × 7 resolution with a screen size of 9 mm × 3.4 mm. Polymer LED pixels can supply a brightness level of 0.3 cd/m2 and an efficiency of %1.
Keywords: Optics.; Quantum optics.